2022
DOI: 10.1029/2021wr031886
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Effects of Multiscale Heterogeneous Sediments on Solute Mixing and Effective Dispersion

Abstract: Accurate representation of solute transport processes (e.g., dispersion, mixing, and dilution) is important for various porous media-related applications such as hydrogeology, soil physics, environmental engineering and sciences, water resources management, and petroleum engineering (de

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 97 publications
0
7
0
Order By: Relevance
“…Dong et al (2018) suggested that solute transport time and pore-scale geometry control the magnitude of the effect of dispersion; thus, it is assumed that advection-induced flow is homogenous most times, leading to an underestimation of the dispersion coefficient. This was further confirmed by Ren et al (2022), who revealed that at meter-scale heterogeneity, effective dispersion is more sensitive to pore-scale heterogeneity. Solute mixing by hydrodynamic dispersion reflects the heterogeneity of the aquifer at a scale smaller than that associated with the measurement of advection.…”
Section: Frontiers In Environmental Sciencementioning
confidence: 57%
“…Dong et al (2018) suggested that solute transport time and pore-scale geometry control the magnitude of the effect of dispersion; thus, it is assumed that advection-induced flow is homogenous most times, leading to an underestimation of the dispersion coefficient. This was further confirmed by Ren et al (2022), who revealed that at meter-scale heterogeneity, effective dispersion is more sensitive to pore-scale heterogeneity. Solute mixing by hydrodynamic dispersion reflects the heterogeneity of the aquifer at a scale smaller than that associated with the measurement of advection.…”
Section: Frontiers In Environmental Sciencementioning
confidence: 57%
“…This information is used to carry out an analysis of the spatial moments of the solute concentration distribution throughout various stages of the experiments. Spatial moment analysis has been proven to be useful measures to describe and analyze the longitudinal spreading of the plumes by, for instance, Trevisan et al and Ren et al Based on our experimental findings, we propose a simplified representation of the mixing process by analogy with the 1D advection-dispersion model. The paper is structured as follows: In section , we introduce the applied materials and the experimental procedure together with the image acquisition and analysis.…”
Section: Introductionmentioning
confidence: 96%
“…By expressing the ratio of density-driven and diffusive mass transport, the dimensionless Rayleigh number, Ra , is commonly used as the basis for the derivation of scaling relationships that predict the occurrence of solutal convection and quantify its strength. Despite it being a fundamental component of convective mixing in porous media, the role of hydrodynamic dispersion is only rarely discussed in experimental studies. Dispersion can act along the main flow direction (longitudinal dispersion) or perpendicular to it (transverse dispersion), thereby affecting the structure of the downwelling fingers. Dispersion has been shown to also reduce the onset time of convection and to contribute to the dissolution process in the presence of a background advective flow. , The characterization of DDC in porous media remains challenging and requires the development and application of advanced laboratory protocols to unravel the evolving concentration field in the medium.…”
Section: Introductionmentioning
confidence: 99%
“…(8,9) Adsorption and dispersion processes form the basis of modeling crude oil contaminants in groundwater pollution. (10) Many studies have shown the impact of crude oil spills on the soil and their seepage into groundwater. Some researchers focused on assessing the quality of groundwater in the study area (Nigeria) with the aim of ascertaining the nature and extent of the effects of the oil spill on that water.…”
Section: Introductionmentioning
confidence: 99%